Respon Pemberian Pupuk Organik Cair (POC) Terhadap Pertumbuhan Dan Hasil Tanaman Selada (Lactuca sativa L.) Pada Hidroponik Sistem Wick - Timoty Toerok Asmin; Tuti Heiriyani; Rabiatul Wahdah (Agroekotek View, 2019)
Lettuce (Lactuca sativa L.) belongs to leaf vegetables with high economic value. However, with the reduction in agricultural land in urban areas because of the transfer of functions to infrastructure and buildings, the number of production has also been reduced, so that the innovation of suitable crop cultivation in cities is needed, one of which is hydroponics. Taking into account the factors of fertilizer prices and urban household waste, water-washed household rice wastes were then raised and banana stumps and chicken manure were combined to become a solution of liquid organic fertilizer which is expected to be an alternative to AB mix fertilizer. This study aims to determine the response of lettuce plants to the administration of LOF and find out the best composition of LOF on lettuce growth. This research was conducted from July to October 2018 in the greenhouse of the Faculty of Agriculture, University of Lambung Mangkurat, Banjarbaru. The design used was a completely randomized design (CRD) of one factor, namely the treatment of the composition of ppm LOF. The results showed that LOF only had a significant effect on wet weight. The best LOF composition in increasing plant wet weight is LOF 450 ppm.